1979
DOI: 10.1111/j.1365-2362.1979.tb01668.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversible abnormalities of low density lipoprotein composition in familial hypercholesterolaemia

Abstract: Low density lipoprotein (LDL) composition was analysed in twenty-one patients with familial hypercholesterolaemia, including six homozygotes. By comparison with nineteen controls the patients' LDL had an increased ratio of cholesterol:phospholipid and a decreased ratio of lecithin:sphingomyelin; these changes were more marked in homozygotes than in heterozygotes. Treatment of sevel patients with plasma exchange temporarily resulted in near-normalization of the composition of their LDL. These results suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…These findings contrast with those in patients with FH, in whom there is an increase in the more buoyant LDL particles, which are relatively cholesterol enriched and protein depleted. The present findings are also consistent with the previous reports of altered LDL in FH (20,(27)(28)(29).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These findings contrast with those in patients with FH, in whom there is an increase in the more buoyant LDL particles, which are relatively cholesterol enriched and protein depleted. The present findings are also consistent with the previous reports of altered LDL in FH (20,(27)(28)(29).…”
Section: Discussionsupporting
confidence: 94%
“…A possible explanation for the decreased cholesterol-toprotein ratio in hyperapoB might be a shift in the spectrum of LDL towards smaller, denser particles. In contrast, LDL from patients with FH has a higher than normal cholesterol-to-protein ratio (20), suggestive of a shift towards larger, less dense particles. To test this hypothesis, we investigated the pattern of distribution of LDL in normal subjects, as well as patients with hyperapoB and FH, by means of density gradient ultracentrifugation.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The increase in SM was related to an increased ratio of free to esterified cholesterol in LDL. The changes were in part reversed after LDL apheresis, when newly produced LDLs predominate, indicating that they are linked to prolonged residence time in plasma for the LDL particles (120,142). The few data on type III human hyperlipidemia also reveal that the accumulation of remnant particles is linked to an increase in SM level in the lipoproteins (143).…”
Section: Causes Of Hypersphingomyelinemiamentioning
confidence: 88%
“…These differences include an increase in the cholesterol/phospholipid ratio, an increase in the proportion of cholesterol esters, and an abnormally low lecithin/sphingomyelin ratio. These acquired changes, which are believed to reflect decreases in the fractional rate of catabolism of LDL, are more pronounced in patients with homozygous FH and can be partially ameliorated by plasma exchange therapy or by treatment with colestipol or cholestyramine (31). Although increases in the cholesterol ester and sphingomyelin content of LDL have been reported to decrease its binding affinity to the high-affinity LDL receptors on cultured human fibroblasts (34), an earlier study (35) showed no difference in the rates of cellular metabolism of LDL isolated from the plasma of normal subjects as compared with that from patients with homozygous FH.…”
Section: Discussionmentioning
confidence: 99%